Vaksin ETEC: Solusi Baru Pencegahan Foodborne Disease: Analisis - Inayah, Ninda; Shofa, Fajria; Alfiattutthoyyibah, Tiara; Mahrunnisa, Fitria (PT Kalbe Farma Tbk., 2025)
Diarrhea remains a leading cause of under-fve mortality globally and in Indonesia. In 2020, the mortality rate for children aged 12-59 months due to diarrhea was 4.55%. Enterotoxigenic Escherichia coli (ETEC) is estimated to cause approximately 220 million episodes of diarrhea annually worldwide. ETEC vaccines are being developed to prevent the acute disease burden and long-term sequelae such as growth and cognitive impairment linked to repeated infections. Public health models suggest that an ETEC vaccine has the potential to reduce 4.2%–6.0% of deaths due to diarrhea, particularly among infants and children in low-resource settings, and decrease antibiotic use, thereby improving treatment cost efciency. This paper reviews ETEC structure and pathogenesis, clinical features, and the current vaccine pipeline focused on colonization factor (CF) antigens and LT/ST toxins. The highlighted leading candidates, including ETVAX (an oral inactivated whole-cell vaccine currently in phase 2b), and multivalent approaches targeting the most prevalent CFs, which could theoretically protect against 70%-80% of circulating disease-causing strains in at-risk populations.